COASTAL ABRASION VULNERABILITY IN SUB-DISTRICT BUNGUS TELUK KABUNG KOTA PADANG - Sri Kandi Putri; Dewi Ramadhan (Remote Sensing Technology Study Program, 2020)
This study aims to analyze the level of coastal abrasion vulnerability in sub-district Bungus Teluk Kabung of Padang City. This type of research is mixed method. The type of data is primary data and secondary data. The primary data obtained from research questionnaires and field observations using interview guidelines while the secondary data consists of identification of critical beaches in West Sumatra, Disaster Event Data, Reports on coastal abrasion disasters, Statistics of sub-district Bungus Teluk Kabung, The technique of analyzing the level of vulnerability of coastal abrasion disaster uses secondary data analysis from the map of coastal abrasion disaster vulnerability from BNPB which refers to the General Guidelines for Disaster Risk Assessment, PERKA BNPB No. 2 of 2012. The vulnerability index scale is divided into 3 categories: low, moderate, high. The results showed that the level of coastal abrasion vulnerability in sub-district Bungus Teluk Kabung was classified into the low category with a vulnerability score of 0.0-0.25, moderate with a vulnerability score of 0.25-0.54 and high which scores between 0.54 - 0.75. Physical vulnerability in all of villages of sub-district Bungus Teluk Kabung is come under low category. Social vulnerability is low and moderate. Environmental vulnerability in the moderate category and economic vulnerability in the high category